2014
DOI: 10.2337/db14-0541
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 Maintains Glucose Homeostasis by Mediating the Cross Talk Between Liver and Brain During Prolonged Fasting

Abstract: Hepatic gluconeogenesis is a main source of blood glucose during prolonged fasting and is orchestrated by endocrine and neural pathways. Here we show that the hepatocytesecreted hormone fibroblast growth factor 21 (FGF21) induces fasting gluconeogenesis via the brain-liver axis. Prolonged fasting induces activation of the transcription factor peroxisome proliferator-activated receptor a (PPARa) in the liver and subsequent hepatic production of FGF21, which enters into the brain to activate the hypothalamic-pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
251
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(263 citation statements)
references
References 38 publications
(49 reference statements)
7
251
5
Order By: Relevance
“…bFGF is another member of the FGF family, whose efficacy in promoting fibroblast-cell migration has been previously described (7). The functions of FGF21 in glucose homeostasis as well as in hepato-and cardioprotection have been reported (9)(10)(11). While it has been reported that FGF21 is highly expressed in the liver (8), the present study revealed that its expression was even higher in the injured skin of mice.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…bFGF is another member of the FGF family, whose efficacy in promoting fibroblast-cell migration has been previously described (7). The functions of FGF21 in glucose homeostasis as well as in hepato-and cardioprotection have been reported (9)(10)(11). While it has been reported that FGF21 is highly expressed in the liver (8), the present study revealed that its expression was even higher in the injured skin of mice.…”
Section: Discussioncontrasting
confidence: 48%
“…Initially, 1, a member of the FGF family, was reported to be preferentially expressed in the liver (8). However, recent studies have identified that FGF21 is inducible by starvation or certain drugs, and have reported on its diverse functions in glucose homeostasis as well as hepatoand cardioprotection (9)(10)(11). FGF19, FGF21 and FGF23 belong to the FGF19 sub-family.…”
Section: Introductionmentioning
confidence: 99%
“…Sirt 1 repression induces mitophagy with the development of MODS and may supersede the connections between diabetic genes (Type 1 and 2) and their associated diseases (Figure 2). Sirt 1 plays an important role in the regulation fibroblast growth factor 21 [82][83][84] and the apelinergic pathway [85] with connections to brain insulin resistance (stroke, dementia, AD) [86]. In Type 2 diabetes the relevance of stress, anxiety and hyperphagia are associated with defective apelinergic pathways [85] and severity of diabetes (post-transcriptional defect) associated with Sirt 1-apelinergic system defects in mental disorders [87].…”
Section: Scn Dysfunction In Diabetes With Relevance To Modsmentioning
confidence: 99%
“…Intracerebroventricular injection of FGF21 in Fgf21-KO mice restores the metabolic effects of FGF21 essentially through the corticotropinreleasing hormone (CRH) and the activation of CREB, which finally enhances hepatic gluconeogenesis and sympathetic nerve activity in BAT [56,61,62]. According to that, lack of KLB in the brain blunts these effects [56,60,61]. Finally, treatment with the b-blocker propranolol diminishes the effects of FGF21 when it is centrally administered but not when delivered peripherally [60].…”
Section: Central Nervous System: Target Tissue Of Fgf21mentioning
confidence: 99%
“…FGF21 has the potential to act in the central nervous system (CNS) since FGFRs are widely expressed in this tissue and KLB is specifically expressed in the suprachiasmatic nucleus, the dorsal vagal complex of the hindbrain, the area postrema, the nucleus tractus solitari, the nodose ganglia, and the paraventricular nucleus [22,55,56]. Immunoblotting experiments have revealed that FGF21 is expressed in several regions of the brain, such as the substantia nigra, striatum, hippocampus, and cortex [57]; however, this growth factor also crosses the blood brain barrier and is present in the cerebrospinal fluid in a linear relationship with serum levels [58].…”
Section: Central Nervous System: Target Tissue Of Fgf21mentioning
confidence: 99%